2022
DOI: 10.1002/cbic.202100625
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Biological Tools for the Study of Voltage‐Gated Sodium Channels in Electrogenesis and Nociception

Abstract: The malfunction and misregulation of voltage‐gated sodium channels (NaVs) underlie in large part the electrical hyperexcitability characteristic of chronic inflammatory and neuropathic pain. NaVs are responsible for the initiation and propagation of electrical impulses (action potentials) in cells. Tissue and nerve injury alter the expression and localization of multiple NaV isoforms, including NaV1.1, 1.3, and 1.6–1.9, resulting in aberrant action potential firing patterns. To better understand the role of Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 290 publications
(506 reference statements)
0
1
0
Order By: Relevance
“…Prior studies [7] revealed that C2’‐substituted maleimide STX conjugates containing pendant alkyl chains retained irreversible binding activity against wild type‐Na V s and were therefore considered an obvious location to introduce a ‘click’ group or affinity tag. Direct incorporation of biotin [9] or a fluorogenic dye [5a,10] was desired as no additional synthetic operations would be required to isolate or visualize toxin‐labeled channels. Toxin‐maleimide‐‘click’ reactive probes, by virtue of the smaller size of the prosthetic groups, might retain a higher affinity for binding to the channel, but would necessitate an extra reaction step following protein alkylation [11]…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies [7] revealed that C2’‐substituted maleimide STX conjugates containing pendant alkyl chains retained irreversible binding activity against wild type‐Na V s and were therefore considered an obvious location to introduce a ‘click’ group or affinity tag. Direct incorporation of biotin [9] or a fluorogenic dye [5a,10] was desired as no additional synthetic operations would be required to isolate or visualize toxin‐labeled channels. Toxin‐maleimide‐‘click’ reactive probes, by virtue of the smaller size of the prosthetic groups, might retain a higher affinity for binding to the channel, but would necessitate an extra reaction step following protein alkylation [11]…”
Section: Resultsmentioning
confidence: 99%